Effect of Bitter Melon's Extract Fraction (Momordica Charantia L.) on Blood Sugar Reduction, Insulin Resistance and Phosphatidyl Inositol 3-Kinase (PI3K) Signalling in Male Rats (Rattus novergicus) Streptozotocin-Induced Hyperglycemia - Gustiany Nadya Damanik (Green Publisher Indonesia, 2024)
Background: Diabetes mellitus (DM) is a metabolic disease characterized by symptoms of hyperglycemia as a result of impaired insulin secretion. The main cause of type 2 diabetes mellitus is metabolic disorders characterized by insulin receptor resistance, reduced ability of β-pancreatic cells to secrete insulin, and abnormalities in insulin secretion from pancreatic β islet of Langerhans cells. In insulin resistance, the presence of impaired signaling in Phosphatidylinositol 3-kinase (PI3K) disrupts glucose regulation in the body. The purpose of this study was to determine the effect of bitter melon extract (Momordica charantia L.) on blood sugar reduction, insulin resistance and phosphatidyl inositol 3-kinase (PI3K) signaling. Purpose : The objectives of this study are Effect of Bitter Melon's Extract Fraction (Momordica Charantia L.) on Blood Sugar Reduction, Insulin Resistance and Phosphatidyl Inositol 3-Kinase (PI3K) Signalling in Male Rats (Rattus novergicus) Streptozotocin-Induced Hyperglycemia Method: This study used a type of laboratory experimental research post-test randomized controlled group design on hyperglycemic male rats (Rattus novergicus). All data analysis is done using SPSS software. Results: Based on research conducted, it is known that bitter melon extract affects blood sugar, insulin resistance and PI3K signaling. Conclusion: Bitter melon extract has potential as an herbal antidiabetic remedy